GC-MS-Based Analysis of Methanol: Chloroform-extracted Fatty Acids from Plant Tissues - Patel, Manish Kumar (Bio Protoc, 2018)
Fatty acids (FAs) are carboxylic acids with long aliphatic chains that may be straight, branched and saturated or unsaturated. Most of the naturally occurring plant FAs contains an even number of carbon (C4-C24). FAs are used in food and pharmacological industries due to their nutritional importance. In addition, FAs are considered as a promising alternative for the production of biodiesel from terrestrial plant biomass. To establish commercial applications, more reliable analytical methods are needed for the identification, quantification, and composition determination of FAs. Here, we describe a relatively rapid and sensitive method for the extraction, identification, and quantification of FAs from a small quantity of plant tissue. The method includes steps of lipid extraction, conversion of lipid to fatty acid methyl esters (FAMEs) by transmethylation, identification and quantification of FAMEs using gas chromatography-mass spectrometry (GC-MS). In this protocol, an internal standard is added prior to GC-MS analysis. The amount of each FA is calculated from its peak area relative to the peak area of the internal standard.